(untitled) (Journal of Information Technology and Digital World, 2020)
Voluntary retirement schemes are observed in certain sectors of the Indian Industry such as Banking and Insurance. There is a need to determine the optimal time to withdraw a voluntary retirement scheme (VRS), balancing the reduction of high compensation of a segment of employees, prevent mass voluntary turnover from the grade, achieve optimal productivity and ensure normal business operations. In this paper an approach to derive an optimal policy to withdraw a voluntary retirement scheme considering a probability of acceptance of a retirement request, cost due to announcing a voluntary retirement scheme and cost to the organisation due to one-time special payments to those who retire during the time period is discussed.